Exposure in Vivo as a Treatment Approach to Target Pain-Related Fear: Theory and New Insights From Research and Clinical Practice. Issue 2 (27th January 2022) - den Hollander, Marlies; Smeets, Rob J E M; van Meulenbroek, Thijs; van Laake-Geelen, Charlotte C M; Baadjou, Vera A; Timmers, Inge
Abstract: : Pain-related fear (PRF) can be a significant factor contributing to the development and maintenance of pain-related disability in individuals with persistent pain. One treatment approach to target PRF and related avoidance behavior is exposure in vivo (EXP). EXP has a long history in the field of anxiety, a field that is constantly evolving. This Perspective outlines recent theoretical advancements and how they apply to EXP for PRF, including suggestions for how to optimize inhibitory learning during EXP; reviews mechanistic work from neuroimaging supporting the targeting of PRF in people with chronic pain; and focuses on clinical applications of EXP for PRF, as EXP is moving into new directions regarding who is receiving EXP (eg, EXP in chronic secondary pain) and how treatment is provided (EXP in primary care with a crucial role for physical therapists). Considerations are provided regarding challenges, remaining questions, and promising future perspectives. Impact: For patients with chronic pain who have elevated pain-related fear (PRF), exposure is the treatment of choice. This Perspective highlights the inhibitory learning approach, summarizes mechanistic work from experimental psychology and neuroimaging regarding PRF in chronic pain, and describes possible clinical applications of EXP in chronic secondary pain as well as in primary care.